POLA PENGASUHAN ANAK PADA KELUARGA SINGLE PARENT - Prayoga, Satria Agus; Hidayati, Dewi Ayu (SOCIOLOGIE, 2013)
The results of this study indicate that the pattern of Single Parent Family Care is not too different from intact families. The analysis showed that the pattern of care by the family and the Single Parent majority use democratic parenting patterns. The basis of this parenting, parents mengedepankansikap tolerance, and good communication between parents and children. Children are given the freedom to develop skills, express their creativity, talent or a possession but parents still gave the control / supervision of the child. But there are several other informants who use authoritarian parenting and liberal parenting.Keywords: Parenting, single parent, child